FDI into Kazakhstan : A comparative analysis of EU and Chinese investments. - Alkenov, Dayan (2025)
This Master thesis focuses on FDIs impacts from China and EU on Kazakhstan economic development. Comparative analysis includes volume and structure of investments, sectoral division and most importantly strategic implications and nature of investments. Moreover, Kazakhstan specifics of geopolitical positioning and investment landscape were also discussed.